MODEL AFIRMATIF BAGI MASYARAKAT PESISIR PANTAI DI WILAYAH JAKARTA UTARA TENTANG BATIK JUMPUTAN BERMOTIF ALAM VERSI MILENIAL - Nadiroh; Hasanah, Uswatun; Husen, Achmad; Zulfa, Vania; Yuliani, Shahibah; Rahmawaty, Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Community service activities are carried out in an effort to strengthen women's capacity so they can develop the jumputan batik home industry and the millennial version of natural fashion designs. Operationally the product of community service activities is jumputan cloth using natural dyes. The training materials for community service activities are the skills of making jumputan batik patterns with natural characteristics, as well as green campaigns on environmental preservation and sustainable lifestyles through getting used to implementing 7R (recycle, reuse, reduce, replace, repair, replant, refill). Counselling on environmental materials in sustainable development was delivered in a planned manner to 27 Coastal Communities in the North Jakarta Region virtually. The community is expected to be able to design skills. In the virtual process, they have shown: enthusiasm, collaboration, curiosity, participation in providing ideas, discipline, new ideas, creativity, interest, ability to express opinions and motivation. The millennial version of natural character fashion products can soon be widely promoted at the local, regional, national and global levels. Demand for fashion products with coastal batik motifs with a millennial version of nature shows the high enthusiasm of coastal communities in North Jakarta for products with the concept of supporting a circular economy by implementing the 7R.